The Credit Hour System As Adapted by the University of Gezira: Special Reference to Medical Faculties - Adam, Hussein S. (Gezira Journal of Health Sciences; Vol 1 No 2 (2005), 2005)
The University of Gezira was established in 1975. The first Batch of students registered for their first semester in September 1978. There were four Faculties at that time: Agricultural Sciences, Economics & Rural Development, Medicine and Science & Technology (Presently Engineering & Technology). There were about 50 students in each Faculty. The teaching was in English. The pioneers opted for a modified American System rather than having a carbon copy of the University of Khartoum with its well established British System. They chose the Credit Hour System adapted to Sudanese environment.